The perceptions and lived experiences of Indonesian nursing students in providing end-of-life care: A qualitative study - Chalita Diandra Natalie; Yenni Ferawati Sitanggang; Oscar Fidel Antunez Martinez (Belitung Nursing Journal, 2026)
Background: End-of-life (EoL) care is a form of service provided to patients in the terminal phase and families to meet physical, psychological, social, and spiritual needs so that patients can face death peacefully and with dignity. EoL care can be facilitated by medical personnel, but it is not uncommon for nursing students to be involved as well. Several factors influence nursing students’ ability to provide EoL care to patients. Objective: This study aimed to explore the nursing students’ perceptions and experiences regarding the provision of EoL care during clinical placements. Methods: A qualitative descriptive study was conducted using purposive sampling and in-depth interviews with 10 professional nursing students who had experience providing EoL care. Data were collected with a four-question guide between February and May 2025 and analyzed inductively using thematic analysis, including familiarization, coding, theme development, and reporting. Strategies to enhance trustworthiness included credibility, transferability, dependability, and confirmability. Results: Four main themes emerged: 1) Nursing Students’ perspective of EoL Care, 2) Providing holistic Care to Patients and Families, 3) Challenges and Opportunities in Providing EoL Care, 4) Developing Heart of Caring. Participants conceptualized EoL as a holistic, person-centered process emphasizing comfort, dignity, and compassion rather than cure. They demonstrated developing competence in identifying clinical indicators of terminal decline and addressing patients’ physical, psychosocial, and spiritual needs. Students described providing comfort through symptom management, active listening, emotional support, and the facilitation of spiritual practices aligned with patients’ beliefs. Although communication difficulties, emotional strain, and insufficient preparation were significant barriers, they were also perceived as valuable learning opportunities that fostered personal growth, empathy, and professional confidence. Spiritual faith and viewing patients as family members further inspired compassionate, value-driven care. Conclusion: Overall, the findings emphasize that experiential and reflective learning during clinical placements are essential in shaping nursing students’ moral sensitivity, resilience, and humanistic orientation. Integrating Structured EoL care education that includes emotional and spiritual dimensions is crucial to preparing future nurses to deliver dignified, compassionate, and holistic care for patients and families at EoL.